2022
DOI: 10.1017/s1360674322000223
|View full text |Cite
|
Sign up to set email alerts
|

Is morphosyntactic agreement reflected in acoustic detail? Thesduration of English regular plural nouns

Abstract: Studies have challenged the assumption that different types of word-final s in English are homophonous. On the one hand, affixal (e.g. laps) and non-affixal s (e.g. lapse) differ in their duration; on the other hand, variation exists across several types of affixal s (e.g. between the plural (cars) and genitive plural (cars’)). This line of research was recently expanded in a study in which an interesting side effect appeared: the s was longer if followed by a past tense verb (e.g. The pods/odds eventually dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Relying on the main effects analysis, we see that while determiner-noun agreement increased response accuracy, noun-verb agreement did not. This finding is in line with Schlechtweg & Corbett's (2023) findings for production. In this previous study, we found that the type of determiner affected the duration of the English plural s suffix.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Relying on the main effects analysis, we see that while determiner-noun agreement increased response accuracy, noun-verb agreement did not. This finding is in line with Schlechtweg & Corbett's (2023) findings for production. In this previous study, we found that the type of determiner affected the duration of the English plural s suffix.…”
Section: Discussionsupporting
confidence: 92%
“…Sentences similar to those in (4) have recently been examined in a production study (see Schlechtweg & Corbett 2023 and (2) above). The present work focuses on perception, relying on the eight sentence versions given in ( 4), that is, on both singular and plural nouns, while the production study from Schlechtweg & Corbett (2023) considered plural nouns only.…”
Section: Psycholinguistic Effects Of Agreementmentioning
confidence: 99%
See 2 more Smart Citations